2016
DOI: 10.1111/clr.12906
|View full text |Cite
|
Sign up to set email alerts
|

Sequential morphometric evaluation at UnicCa® and SLActive® implant surfaces. An experimental study in the dog

Abstract: The patterns of healing at highly hydrophilic surfaces occurred through the early formation of a provisional matrix followed by the formation of new bone and marrow at various stages of maturation. The healing was similar to those described in different animal models, anatomical sites and surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The emergence of dental implants with reduced dimensions is the net outcome of several factors (material science, surface properties, and macro-design of the implant shape and connection) that converge in improving their biological and mechanical properties [41][42][43][44][45][46]. This has also been accompanied by a better understanding of the biomechanical behavior of the restoration-implant-bone under function [47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of dental implants with reduced dimensions is the net outcome of several factors (material science, surface properties, and macro-design of the implant shape and connection) that converge in improving their biological and mechanical properties [41][42][43][44][45][46]. This has also been accompanied by a better understanding of the biomechanical behavior of the restoration-implant-bone under function [47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that plasma rich in growth factors may stimulate faster epithelization, reduce postoperative pain and symptoms, and enhance hard and soft tissue healing in a number of oral surgery procedures in both healthy and medically compromised subjects [ 1 , 2 , 14 , 17 , 18 , 19 , 24 , 25 , 26 , 42 , 46 , 48 , 49 , 50 , 51 ]. Favero et al in a study on animal model of implant osseointegration, reported that the percentages of new bone increased by 4 times after 2 weeks at the UnicCa ® surface, and higher new bone percentages were found at BTI UnicCa ® , which immediately initiates the regenerative process and reduces implant failure [ 52 , 53 ]. Though, in spite of convincing preclinical evidence, the actual benefit of the adjunctive use of platelet concentrates in implant treatment needs to be supported by further evidence-based, long-term clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with other studies that evaluated bone density at implants at various periods of healing. In experimental studies in dogs [32,33], different implant surfaces were evaluated after 1, 2, 4, and 8 weeks of submerged healing. New bone density was found increasing in percentages over time.…”
Section: Discussionmentioning
confidence: 99%